The Descriptive Analysis of Students’ Ability in Translating Analytical Exposition Text at the Eleventh Grade of SMA Negeri 1 Gunungsitoli in 2022/2023 - Agnes Jessica Lase; Trisman Harefa; Elwin Piarawan Zebua; Afore Tahir Harefa (Departement of Mathematics Education, 2023)
The purpose of this study is to analyze the students’ ability in translating analytical exposition text at the eleventh grade of SMA Negeri 1 Gunungsitoli. This research used descriptive research approach. The data was students’ translation analytical exposition text by eleventh grade of SMA Negeri 1 Gunungsitoli. The instrument that used to collect the data were test and questionnaire sheet. The data was analyzed by using translation scoring rubric that consist of three main aspect, namely: Accuracy, Readability, and acceptability. Furthermore, the researcher presented the data with percentage of scoring and described it into a description paragraph. The result of study showed that students’ score in translating analytical exposition text was 44,8. From the questionnaire, this research showed the students difficulties in translating long sentences was the most prominent factors that caused the students have difficulties in translating the text with the highest percentage was 63,8%. Based on the result of this research, the researcher suggest that the teacher should give more exercise or practice in translation activity, so that the students can overcome the difficulties that students face and make a good translation without difficulties.